Removal of 142Pr from nuclear purity water using hydroxyapatite. Issue 7 (22nd July 2022) - Solache-Ríos, M.; Jiménez-Reyes, M.; Almazán-Sánchez, P. T.
Abstract: The adsorption of praseodymium using hydroxyapatite was evaluated. The hydroxyapatite (HAP) was characterized by X-ray diffraction (JCPDS 01-04-3708), scanning electron microscopy, BET specific surface area (54.2 m 2 /g), and point of zero charge (6.5). Adsorption kinetics and isotherms were evaluated at pH of 3 and 142 Pr was determined using a gamma spectrometer. The adsorption of praseodymium was fast (1 min of contact) with an adsorption capacity of 1.68 mg/g and the data were best adjusted to the pseudo-second-order model, whereas the data of adsorption isotherm were best adjusted to the Langmuir model with a maximum adsorption capacity of 39.16 ± 0.20 mg/g. The thermodynamic parameters indicated that a physicochemical mechanism took place in the adsorption of praseodymium by HAP (adsorption enthalpy = 31.65 kJ/mol), the randomness of the system increased (adsorption entropy = 0.16 kJ/mol), and according with Gibbs free energy, the adsorption process was spontaneous at high temperature. The praseodymium in the hydroxyapatite is stable, it could not be desorbed using different solutions (ammonium sulfate, calcium chloride, sodium chloride, hydrochloric acid, and sodium hydroxide).